Sickness absence in a re-employment program as a predictor of labor market attachment among long-term unemployed individuals: A 6-year cohort study in Finland - Nwaru, Chioma A.; Kivimäki, Mika; Pentti, Jaana; Vahtera, Jussi; Virtanen, Pekka (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'We examined whether sickness absence during participation in a state subsidized re-employment program among long-term unemployed people was associated with subsequent labor market attachment. ' ' METHODS ': 'We linked 18 944 long-term unemployed participants (aged 18–60 years) of a six-month subsidized re-employment program in Finland to their records of sickness absence during the program and labor market status after the program. We used the latent class growth model to identify labor market attachment trajectories over a six-year follow-up period and multinomial logistic regression to investigate the association between sickness absence and labor market attachment trajectories. ' ' RESULTS ': 'We identified four labor market attachment trajectories: "strengthening", (77%), "delayed" (6%), "leavers" (10%), and "non-attached" (7%). Sickness absence was associated with an increased risk of belonging to the leavers and non-attached trajectories. Having >30 days of sickness absence during the six-month re-employment program increased the risk for belonging to the future non-attached trajectory in all age groups, but in particular for those aged 30–44 [odds ratio (OR) 7.35, 95% confidence interval (CI) 4.85–11.14] and 18–29 years (OR 5.38, 95%CI 3.76–7.69). At these ages, having fewer than 30 days sickness absences was also associated with an elevated risk of belonging to the non-attached trajectory, while this risk was lower for those aged 45–60. ' ' CONCLUSIONS ': 'Sickness absence during participation in a subsidized re-employment program increased the risk for poor labor market attachment during the subsequent six years. The risk was particularly high among younger participants with >30 days of sickness absence.
Keywords: cohort study; employability; employment trajectory; Finland; health; labor market attachment; long-term unemployed; poor health; re-employment; re-employment program; sickness absence; unemployment